Formation of core@multi-shell CdSe@CdZnS–ZnS quantum dot heterostructure films by pulse electrophoresis deposition. (July 2015) - Raj, Sudarsan; Yun, Jin Hyeon; Adilbish, Ganpurev; Ch, Rama Krishna; Lee, In Hwan; Lee, Min Sang; Yu, Yeon-Tae
Highlights: Pulse EPD technique was used for deposition of CdSe@CdZnS–ZnS QDs. The deposition amount increased with prolonged deposition time. Ethanol is the better solvent medium as compared to 2-propanol. Abstract: CdSe@CdZnS–ZnS core@multi-shell quantum dot (QD) heterostructures were deposited on fluorine doped tinoxide (FTO) glass substrate by pulse electrophoresis deposition (EPD). Field emissions scanning electron microscopy (FESEM) images reveal that the number of QDs deposited on the substrate increased with prolonged deposition time. Ethanol is the better solution medium as compared to 2-propanol for pulse electrophoresis deposition. For longer deposition time the intensity of photo luminescence (PL) peak increased.